Kajian Tingkat Kepuasan Pengguna Jasa terhadap Kinerja Pelayanan Angkutan Penyeberangan Lintas Kariangau – Penajam, Balikpapan - Darmadi Darmadi; Muhammad Zainul Arifin; Imma Widyawati Agustin (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2016)
The objectives of this study are for knowing costumer satisfaction level of ferry service performance Kariangau– Penajam trajectory, Balikpapan based on customer perception with existence of change of ship operational system from 8:4 (8 ship operated and 4 standby) become 10:2 (10 ship operated and 2 standby) and also for getting alternative solution to overcome problems which there is still after imposed of new ship operational system. This study uses Importance-Performance Analysis (IPA) and Customer Satisfaction Index (CSI)methods. Result of study pursuant to analysis of IPA quadrant, service attributes becoming major priority to be improve repaired by its performance are attribute hygiene of bath room/toilet in ship , accuracy of arrival time in destination port, accuracy of time voyage duration, condition of air circulation in ship and demonstration of usage of safety appliance in ship. CSI calculation result based on customer perception obtained value 69% that representation that assessment of respondent to ferry service performance of Kariangau – Penajam trajectory enter in satisfied category.